2020
DOI: 10.1101/2020.11.24.392191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput phenotyping methods for quantifying hair fiber morphology

Abstract: Quantifying the continuous variation in human scalp hair morphology is of interest to anthropologists, geneticists, dermatologists and forensic scientists, but existing methods for studying hair form are time-consuming and not widely used. Here, we present a high-throughput sample preparation protocol for the imaging of both longitudinal (curvature) and cross-sectional scalp hair morphology. Additionally, we describe and validate a new Python package designed to process longitudinal and cross-sectional hair im… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…A recent study of hair originating from people from mixed European and African origin ( n = 140) suggested that there was no causal effect between hair curl and ellipticity once the effect of hair origin was removed [19] thus, for the time being, geometric fibre characteristics should only be viewed as independent.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of hair originating from people from mixed European and African origin ( n = 140) suggested that there was no causal effect between hair curl and ellipticity once the effect of hair origin was removed [19] thus, for the time being, geometric fibre characteristics should only be viewed as independent.…”
Section: Methodsmentioning
confidence: 99%
“…With regards to hair texture, the most common classification is straight, wavy, curly, and sometimes the addition of a “frizzy” category or further subdivisions within these qualitative descriptors (Adhikari et al, 2016; Liu et al, 2018). These qualitative descriptors are inconsistently interpreted and mask the range of variation that exists within tightly curled or “frizzy” hair (Lasisi et al, 2020).…”
Section: Classification and Distortionmentioning
confidence: 99%
“…Yet, what we know about hair biology suggests that variation is more complex than the asserted racial classifications suggest (Adeola et al, 2020;Khumalo, 2007;Lasisi et al, 2016Lasisi et al, , 2020Loussouarn et al, 2007). Various studies of hair fiber curvature and cross-sectional geometry show continuous variation across populations (Fujimoto et al, 2008;Hrdy, 1973;Lasisi et al, 2016;Loussouarn et al, 2007).…”
Section: Objective Variation and Subjective Saliencementioning
confidence: 99%